ENGINEERING EXPERTS PROVIDE SOLUTIONS TO REPAIR TUBE WELLS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KOTA BHARU, 8 January 2015 A group of 9 academicians, assistant engineers and officers of the Universiti Sains Malaysia (USM) School of Civil Engineering and one from the School of Materials and Mineral Resources Engineering together with a PhD candidate led by the expert in water treatment and supply, Professor Dr. Mohd. Nordin Adlan was among the volunteers who help in the aftermath of the floods in Kelantan.